KONDILEKTOMI PADA PENDERITA DEWASA DENGAN ANKILOSIS SENDI TEMPOROMANDIBULA - Bambang Aries Purbawanto; Alwin Kasim; Sunardi Mangunjaya (Faculty of Dentistry, Universitas Indonesia, 2015)
Ankylosis of the temporomandibular joint is a fusion of the glenoid fossa and capsular surface of the joint that involved condyle and discus as a result of the formation of fibrous tissue or bone formation. This condition caused the mandible could not translate from the fossa. This condition reduced mouth opening that range from partial to complete immobility of the jaw. Ankylosis can be divided into two types, intracapsular and extracapsular ankylosis. This case reported a condylectomy of an adult patient with ankylosis for eight years. It resulted maximum opening mouth approximately 32 mm.